2016
DOI: 10.14202/vetworld.2016.1039-1042
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of polymerase chain reaction assay with microscopy for detection of asymptomatic carrier state of theileriosis in a herd of crossbred cattle

Abstract: Aim:This study aims to develop and to standardize a polymerase chain reaction (PCR) assay that will diagnose clinical as well as carrier state of the disease and to compare the results with conventional microscopy technique.Materials and Methods:A herd of crossbred cattle with the previous history of theileriosis in village Lahli, district Rohtak, Haryana, was selected for this study. A total of 29 blood samples were collected randomly from cows including five clinically ill cattle. Blood smears from all anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
3
5
0
Order By: Relevance
“…Our result recorder 88% rate by PCR and 39.33% microscopically, these agreed with many researchers, (28) in Turkey and (29) in India, the differences between microscopic and molecular methods attributed to several reasons as chronic and carrier cases with low parasitemia and parasite misdiagnosis with staining artifacts (30). Phylogenetic analysis confirmed low differences between Iraqi strains of Theileria annulata and other countries .…”
Section: Resultssupporting
confidence: 91%
“…Our result recorder 88% rate by PCR and 39.33% microscopically, these agreed with many researchers, (28) in Turkey and (29) in India, the differences between microscopic and molecular methods attributed to several reasons as chronic and carrier cases with low parasitemia and parasite misdiagnosis with staining artifacts (30). Phylogenetic analysis confirmed low differences between Iraqi strains of Theileria annulata and other countries .…”
Section: Resultssupporting
confidence: 91%
“…As well as, PCR is much more sensitive in clinically infected, apparently healthy animals (carriers) and in the early phase of infection. This agree with Charaya et al (2016) reported that PCR assay showed no cross-reactivity with theileria sp. and can be used specifically to diagnose theileriosis in herd and differentiate it from other hemoprotozoan diseases.…”
Section: Discussionsupporting
confidence: 93%
“…As shown in Table 2, DreamTaq Green PCR master mix (2x) was cheapest of Taq polymerase. This Taq polymerase further has been reported to also be applied for some PCR routine check application (Charaya et al 2016). However, as one of the commercial Taq polymerases, DreamTaq Green PCR master mix (2x) is susceptible to DNA contamination.…”
Section: Discussionmentioning
confidence: 99%